Chitosan nanoparticles-encapsulated cannabis extracts and their antimicrobial potential against skin pathogens - Skala, Tomáš; Ventura, Jordi; Morellá-Aucejo, Ángela; Fraňková, Adéla; Llopis-Lorente, Antoni; Bernardos, Andrea; Tauchen, Jan; Kahánková, Zdeňka; Hubka, Vít; Klouček, Pavel (Frontiers in Medicine, 2025)
Cannabis compounds are well-known for their therapeutic applications in the treatment of various health issues. These substances, mainly cannabinoids, are known for their antimicrobial properties and ability to interact with various cells through endocannabinoid receptors. However, the limitations of cannabis extract, particularly its viscosity, stickiness, and low bioavailability when applied topically, limit its use in dermatology. To enhance topical applications for treating bacterial infections and dermatophytosis, cannabis extracts were encapsulated in chitosan nanoparticles, an easily accessible and cost-effective. Cannabis extracts were prepared from three cannabis strains differing in content of major cannabinoids, namely Chocolope (THCA-A), Jonas 1 (CBDA), and Hemp G (CBGA), and subsequently were encapsulated in chitosan nanoparticles. The resulting particles were characterized, and antimicrobial and cytotoxic activity was evaluated. The mean size of particles ranged from 89.1 ± 24.8 nm for empty nanoparticles to 355.6 ± 101.6 nm for particles containing Hemp G extract. Considering the extract:chitosan ratio (1:10 w/w, 1:20 w/w respectively) and the encapsulation efficiency (EE) range from 44.65 ± 4.39% to 94.44 ± 0.93%, total amount of extracts encapsulated in chitosan nanoparticles ranged from 2.96 ± 0.05 to 5.61 ± 0.19% in 1 g of chitosan nanopowder. Most significant antimicrobial effect was observed against the fungi Nannizzia fulva CCF 6025, where the MIC80 of the pure extract from Jonas 1 variety was 256 μg/mL while the encapsulated extract in chitosan nanoparticles (1:10 w/w extract:chitosan ratio) inhibited growth at a concentration of 256 μg/mL of nanoparticles (corresponding to 13.05 ± 0.13 μg/mL of extract). Overall, encapsulation reduced the amount of extract required to inhibit the growth of pathogenic microorganisms by up to several times, notably in case of dermatophytes, compared to non-encapsulated extracts. Encapsulation also reduced the cytotoxic effects of the extracts on human keratinocytes. Furthermore, pure high-THCA-A extract and encapsulated extract in chitosan nanoparticles slightly increased cell viability after 72 h exposure in low concentrations compared to control. These results may suggest the chitosan nanoparticles-encapsulated formulations as a suitable topical delivery form of cannabis extracts, offering a possible adjunctive treatment of dermatophytosis and wound healing.